EFEKTIVITAS MEDIA INTERAKTIF ETHMAMENKU BERBASIS ANDROID UNTUK MENINGKATKAN PEMAHAMAN KONSEP METEMATIS - Suryani, Desy; Wanabuliandari, Savitri; Ardana Riswari, Lovika (Prodi Pendidikan Matematika Universitas PGRI Ronggolawe, 2024)
This research was motivated by problems in mathematics learning, namely the lack of student understanding of mathematical concepts, one of the causes is the use of learning media or teaching materials that still use print media such as LKS and textbooks, and the learning process that occurs is still teacher-centered. The purpose of this study was to determine the effectiveness of the android-based interactive media Ethmamenku (Etnomatematika Menara Kudus) to improve the ability to understand mathematical concepts. This type of research is Research and Development using the ADDIE development model. The types of data collected are qualitative data and quantitative data. Data analysis in this study used normality gain test analysis. The results of the study suggest that the interactive media Ethmamenku (Etnomatematika Menara Kudus) based on android is declared effective to improve the understanding of mathematical concepts. Judging from the results of limited trials and extensive trials, the results of the n-gain test show that there is a difference or increase between values before and after using the media. Based on these results, the android-based interactive media Ethmamenku (Etnomatematika Menara Kudus) is effectively used in the process of teaching and learning activities.